Phosphatidylserine, inflammation, and central nervous system diseases - Ma, Xiaohua; Li, Xiaojing; Wang, Wenjuan; Zhang, Meng; Yang, Bo; Miao, Zhigang (Frontiers in Aging Neuroscience, 2022)
Phosphatidylserine (PS) is an anionic phospholipid in the eukaryotic membrane and is abundant in the brain. Accumulated studies have revealed that PS is involved in the multiple functions of the brain, such as activation of membrane signaling pathways, neuroinflammation, neurotransmission, and synaptic refinement. Those functions of PS are related to central nervous system (CNS) diseases. In this review, we discuss the metabolism of PS, the anti-inflammation function of PS in the brain; the alterations of PS in different CNS diseases, and the possibility of PS to serve as a therapeutic agent for diseases. Clinical studies have showed that PS has no side effects and is well tolerated. Therefore, PS and PS liposome could be a promising supplementation for these neurodegenerative and neurodevelopmental diseases.